Operative and Oncological Outcomes Comparing Sentinel Node Mapping and Systematic Lymphadenectomy in Endometrial Cancer Staging: Meta-Analysis With Trial Sequential Analysis - Gu, Yu; Cheng, Hongyan; Zong, Liju; Kong, Yujia; Xiang, Yang (Frontiers in Oncology, 2021)
Objective To evaluate the utility of sentinel lymph node mapping (SLN) in patients with endometrial cancer (EC) in comparison with lymphadenectomy (LND). Methods A comprehensive search was performed in MEDLINE, EMBASE, CENTRAL, OVID, Web of Science databases, and three clinical trial registration websites, from the database inception to September 2020. The primary outcomes included operative outcomes, nodal assessment, and oncological outcomes. The software RevMan 5.3 was used. Trial sequential analysis (TSA) and Grading of Recommendations Assessment, Development, and Evaluation (GRADE) were performed. Results Overall, 5820 patients with EC from 15 studies were pooled in the meta-analysis: SLN group (N=2152, 37.0%) and LND group (N=3668, 63.0%). In the meta-analysis of blood loss, SLN offered advantages over LND in reducing operation bleeding (I2 = 74%, P<0.01). The Z-curve of blood loss crossed trial sequential monitoring boundaries, although it did not reach the TSA sample size. There was no difference between SLN and LND in intraoperative complications (I2 = 7%, P=0.12). SLN was superior to LND in detecting positive pelvic nodes (P-LN) (I2 =36%, P <0.001), even in high-risk patients (I2 =36%, P=0.001). However, no difference was observed in the detection of positive para-aortic nodes (PA-LN) (I2 =47%, P=0.76), even in high-risk patients (I2 =62%, P=0.34). Analysis showed no difference between the two groups in the number of resected pelvic nodes (I2 = 99%, P=0.26). SLN was not associated with a significantly different overall survival (I2 =79%, P=0.94). There was no significant difference in progression-free survival between the SLN and LND groups (I2 =52%, P=0.31). No difference was observed in recurrence rate. Based on the GRADE assessment, we considered the quality of current evidence to be moderate for P-LN biopsy, low for items such as blood loss, PA-LN positivity. Conclusion The present meta-analysis underlines that SLN is capable of reducing blood loss during operation, regardless of the surgical approach with firm evidence from TSA. SLN mapping is preferred for less node dissection and more detection of positive lymph nodes even in high-risk patients with conclusive evidence from TSA. The utility of SLN yields no survival detriment in patients with EC.